2021
DOI: 10.1007/s43032-021-00487-5
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and Quality of Life in Women Undergoing First Surgery for Endometriosis: Differences Between Chinese and Italian Population

Abstract: An observational cross-sectional study was conducted in a group (n = 371) of fertile age women with endometriosis, by administering a structured questionnaire, in order to evaluate the incidence of gynecological and systemic comorbidities and the impact on quality of life (QoL) in two different groups of Italian and Chinese patients affected by endometriosis. Chinese (n = 175) and Italian (n = 196) women were compared regarding systemic (inflammatory, autoimmune, and mental) and gynecological comorbidities, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…A recent study has demonstrated that QoL of women with endometriosis may be related also to the ethnicity, the different health system organization and the social and cultural background. Italian women seemed to be more commonly affected by systemic comorbidities, especially inflammatory diseases and mental health disorders (such as depression and anxiety) compared to Chinese population [47].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A recent study has demonstrated that QoL of women with endometriosis may be related also to the ethnicity, the different health system organization and the social and cultural background. Italian women seemed to be more commonly affected by systemic comorbidities, especially inflammatory diseases and mental health disorders (such as depression and anxiety) compared to Chinese population [47].…”
Section: Discussionmentioning
confidence: 92%
“…1) [29,31]. This is particularly important in presence of DIE phenotype because it is more frequently linked to a more severe and aggressive clinical presentation, with an increased rate of intractable chronic pelvic pain, severe dyspareunia, bowel occlusion and hydroureteronephrosis [47].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of QoL was not a scope of our study, but it is interesting that the individual perception of psychophysical well-being improved in all women who breastfed, and particularly in those who exclusively breastfed. This effect may be related not only to pain improvement, but also to the emotional impact associated with breastfeeding [50].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the impact of specific endometriotic lesions was hampered by two things: first, the surgical reports and the recording of lesion characteristics were not uniform, due to different expertise in different hospitals; second, finding a clear association between specific endometriotic lesions and associated pain was complicated by women having multiple lesions rather than isolated endometriotic lesions. Because socio-cultural factors have been shown to influence pain perception (Chen et al, 2021;Facchin et al, 2015), our predominantly Caucasian study group limits generalisability.…”
Section: Strengths and Limitationsmentioning
confidence: 99%